ECOBRICK INOVATIF: MENGUBAH SAMPAH PLASTIK MENJADI WAJAH DESA PUSE KABUPATEN TOLITOLI - Karmila Risa; Ista Dewi; Apriyani Apriyani; Artika Artika; Nurlia Nurlia; Taqwa Taqwa; Mohammad Sawir; Rian Christian Sondakh (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The problem of plastic waste has become a national issue that requires serious attention, including in Tolitoli Regency. The local government continues to strive to improve overall waste management. Plastic that is difficult to decompose can pollute the soil, water, and air, and harm public health. Therefore, innovative strategies are needed that are not only able to reduce the volume of waste but also provide tangible benefits to the community. This community service aims to increase public awareness about the importance of creative and sustainable plastic waste management. The activity was carried out in January–February 2025 in Puse Village, South Dampal District, Tolitoli Regency, involving village officials, youth organisations, and the community. The implementation method included socialisation, plastic waste collection, ecobrick making training, and assembling ecobricks on an iron frame to form a village nameplate. The activity results showed an increase in public awareness in waste management, new skills in ecobrick making, and the realisation of an aesthetic and functional ecobrick-based village nameplate. This community service concludes that the ecobrick method has proven effective as a strategy for reducing plastic waste and strengthening village identity. With active community participation, this activity has the potential to be replicated in other villages as a model of sustainable, environmentally friendly innovation